2021
DOI: 10.1136/gutjnl-2020-323371
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-associated deficits in inhibitory control are phenocopied to mice through gut microbiota changes in one-carbon and aromatic amino acids metabolic pathways

Abstract: BackgroundInhibitory control (IC) is critical to keep long-term goals in everyday life. Bidirectional relationships between IC deficits and obesity are behind unhealthy eating and physical exercise habits.MethodsWe studied gut microbiome composition and functionality, and plasma and faecal metabolomics in association with cognitive tests evaluating inhibitory control (Stroop test) and brain structure in a discovery (n=156), both cross-sectionally and longitudinally, and in an independent replication cohort (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…Interestingly, when mice on a standard chow diet received microbiota from HFD-induced obese mice, they showed increased inflammation, gut permeability, blood-brain barrier (BBB) permeability, anxiety and decreased memory performance ( Bruce-Keller et al, 2015 ). Furthermore, mice that received microbiota from humans experiencing obesity, showed decreased inhibition, just like the human donors, compared to lean human donors and mice who received their microbiota ( Arnoriaga-Rodriguez et al, 2021 ). Altogether, this indicates the importance of a healthy gut microbiota for optimal cognitive function in animals.…”
Section: Gut Microbiome In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, when mice on a standard chow diet received microbiota from HFD-induced obese mice, they showed increased inflammation, gut permeability, blood-brain barrier (BBB) permeability, anxiety and decreased memory performance ( Bruce-Keller et al, 2015 ). Furthermore, mice that received microbiota from humans experiencing obesity, showed decreased inhibition, just like the human donors, compared to lean human donors and mice who received their microbiota ( Arnoriaga-Rodriguez et al, 2021 ). Altogether, this indicates the importance of a healthy gut microbiota for optimal cognitive function in animals.…”
Section: Gut Microbiome In Obesitymentioning
confidence: 99%
“…Firmicutes bacteria are positively associated with memory performance, whereas Bacteroidetes and Proteobacteria are inversely associated with memory ( Arnoriaga-Rodriguez et al, 2020 ). Adults with obesity showed lower scores in a Stroop test, which was positively associated with Eubacterium and Firmicutes bacterium abundance, and inversely associated with Bacteroidetes abundance ( Arnoriaga-Rodriguez et al, 2021 ). One way the gut microbiota may influence cognition is through inflammation: Kreutzer et al (2017) found increased inflammation in the mediobasal hypothalamus in adults with obesity, which was inversely correlated to Parasutterella sp.…”
Section: Gut Microbiome In Obesitymentioning
confidence: 99%
“…D-Glutamine concentrations were shown to be decreased in obese individuals and glutamine supplementation may alleviate obesity symptoms [133, 134]. Metabolic pathways enriched in the microbiota of obese individuals included one-carbon metabolism, which was previously shown to contribute to the development of obesity[135]. In addition, steatosis was shown to be associated with one carbon metabolism’s gene expression [136].…”
Section: Discussionmentioning
confidence: 99%
“…Among microbiota-derived metabolites, several are thought to exert neuroactive properties including short chain fatty acids (SCFA) or bile acids [ 12 , 13 ]. Recent studies highlighted that some gut-derived metabolites originating from aromatic amino acids metabolism are able to modulate cognition and brain function in obesity [ 14 , 15 ]. Since a crosstalk exists between the gut microbiota and the brain, the circulating metabolome is susceptible to play an important role in psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%